Challenges of Effective Implementation of the Universal Basic Education (UBE) Curriculum for Sustainable Development in Nigeria - Ibrahim, Ahmed; Musa,, A. M; Biwai,, Y.; Isah,, A. T. (Kashere Journal of Education, 2021)
The introduction of the Universal Basic Education (UBE) in 1999 was in fulfillment of the stipulation of the world conference on “Education for All”. The basic education is aimed at equipping every Nigerian child with functional knowledge, skills and attitude to live a meaningful and fulfilling live and to contribute to the development of their society in social economic and cultural benefits and to discharge their civic obligations effectively. It was backed up with the UBE curriculum implementation guidelines using the necessary mechanisms. However, the implementation of the UBE curriculum was frauted with some problems ranging from poor funding, inadequate infrastructure facilities and instructional materials, poor quantity and quality of teachers especially in the specialized subject areas and poor monitoring, supervision and evaluation of the UBE curriculum implementation. In view of the above assertion the government should make frantic effort to provide the required materials to ensure effective implementation of the basic education programme to achieve sustainable development.